Immunogenicity and safety of 3-dose primary vaccination with combined DTPa-HBV-IPV/Hib in Indian infants. Issue 1 (2nd January 2017) - Lalwani, Sanjay K.; Agarkhedkar, Sharad; Sundaram, Balasubramanian; Mahantashetti, Niranjana S.; Malshe, Nandini; Agarkhedkar, Shalaka; Van Der Meeren, Olivier; Mehta, Shailesh; Karkada, Naveen; Han, Htay Htay; Mesaros, Narcisa
ABSTRACT: Multivalent combination vaccines have reduced the number of injections and therefore improved vaccine acceptance, timeliness of administration and global coverage. The hexavalent diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus/ Haemophilus influenzae type b (DTPa-HBV-IPV/Hib; Infanrix hexa ™) vaccine, administered according to various schedules, is widely used for the primary vaccination of infants worldwide. In the current publication, we are presenting the immunogenicity and safety of 3 doses of DTPa-HBV-IPV/Hib vaccine when administered to Indian infants. 224 healthy infants (mean age 6.8 weeks) were vaccinated at 6–10–14 weeks (W) of age (n = 112) or 2–4–6 months (M) of age (n = 112). One month after the third vaccine dose, the seroprotection/seropositivity status against diphtheria, pertussis, tetanus, polio, hepatitis B and Hib antigens ranged from 98.6% to 100% in both groups. The vaccine response rate to the pertussis antigens ranged from 97% to 100%. Pain (6–10–14W group: 25.2%; 2–4–6M group: 13.4%) and fever (15.3% and; 15.2%, respectively) were the most frequently reported solicited local and general symptoms. Unsolicited adverse events were reported for 35.7% (6–10–14W group) and 22.3% (2–4–6M group) of subjects. No vaccine related serious adverse events were reported. In conclusion, the hexavalent DTPa-HBV-IPV/Hib vaccine was immunogenic and well tolerated, irrespective of the dosing schedule.